GREEN PURCHASE INTENTION AND BEHAVIOR AMONG MILLENNIAL COFFEE SHOP CUSTOMERS - Driantama Djaelani, Dietta; Vincentia Paundri Negari; Daniel Cuaca (Dinasti Publisher, 2020)
The main purpose of this research is to identify the environmental concern, attitude towards the environment and attitude towards the green product to green purchase intention and green purchase intention and behavior of Millennial Coffee Shop customers in Jakarta and Tangerang. Data gathering is done by online questionnaire through google form and given to respondents that usually purchase coffee in coffee shops with ages 18-36 years old. This research is using SEM (Structural Equation Modeling) to analyze the model with Software SmartPLS 2.0 M3 for data processing. Results from this research shows that there are significant influences between attitude towards green product towards green purchase intention and green purchase intention towards green purchase behavior. While environmental concern and attitude towards the environment did not have significant influence towards green purchase intention.